The EFFECTIVENESS OF SYNTHETIC-BASED CREATIVE WRITING LEARNING MODEL - Moh. Rakhmat (Program Pascasarjana Universitas Negeri Jakarta, 2020)
This research was conducted as an effort to develop a learning model that can improve students' writing skills. The underlying problem of research is the gap between curriculum demands and the condition of students' writing ability is still low. The fundamental problem in this research is how is the model of creative writing learning in accordance with the characteristics of students and how also the learning model is synergized with the synthetic approach. Therefore, this study develops a creative learning model based on synthetic writing to improve writing skills through learning activities in accordance with the requirements of the curriculum. To answer the above problems used research and development methods (research and development), namely research that uses a process to develop the validity of educational products. Developed products include not only learning materials but also procedures and processes defined such as methods, media, learning organizing strategies, and evaluations. The product that will be generated from this research is a creative learning model based on synthetic